Prediction of Self-Perception of Patient in Rheumatoid Arthritis With the Key RNAs Expression Profiles - Wen, Jianting; Liu, Jian; Wang, Bing; Jiang, Hui; Wan, Lei; Xin, Ling; Sun, Yue; Sun, Yanqiu; Zhang, Ying; Du, Xinlei; Wang, Xin; Wang, Jie (Frontiers in Medicine, 2020)
Self-perception in patients is their self-response to sensory stimuli. It is an important aspect of the existence and quality of life among patients. However, the inherent relationship between self-perception and the cellular activity at the molecular level is elusive. In this study, we aimed to explore the association of self-perception with RNA expression profile in patients with rheumatoid arthritis (RA) through computational analysis. We recruited 30 patients clinically diagnosed with RA and to age- and sex-matched controls without previous clinical history. In total, 5 self-perception measures and 30 RNA expression measures were derived from RA patients and control groups. A correlation analysis based on Spearman correlation and Logistic-regression methods was adopted to assess the correlation between self-perception and RNA expression. Quantitative analysis revealed that RA patients with poor self-perception were closely associated with RNAs expression, In addition, 3 key molecules including AC019117.2, LINC00638, and hsa_circ_0003972 could be used to predict self-perception changes in RA patients. Herein, our results will provide new insights in RA diagnosis however, the underlying mechanisms need to be further explored.